Direct approach to the nasal cavity through a bone flap for the treatment of a large nasal cyst. (14th May 2016) - Bolz, N.; Bucheli, M.; Fürst, A. E.; Del Chicca, F.; Jackson, M. A.
Summary: A 21‐year‐old Warmblood mare was referred to the Equine Department, Vetsuisse Faculty, University of Zurich, because of recurrent unilateral nasal discharge 3 months after partial removal of a large cyst from the left maxillary and frontal sinuses. Endoscopic, radiographic and computed tomographic examinations showed that the remnant of the cyst, which originally had extended from the left maxillary and frontal sinuses into the left nasal cavity, had expanded and was obliterating the left middle nasal meatus. A direct surgical approach to the cyst through the left nasal and maxillary bones rostral to the facial crest was chosen, which allowed evaluation and removal of the entire cyst. Endoscopic examination 3 days post operatively showed no remnants of the cyst, and the mare was discharged in good health. Re‐examination one year later showed no recurrence of the cyst.